Experiencias de paisaje: tradición y contemporaneidad en el paisajismo chileno actual (REVISTA NODO, 2009)
Among the conspicuous Chilean architectural production of the last two decades it is possible to find the seeds of a new-born sensibility towards landscape and open spaces. The works presented in the following article depict a greater concern towards social and environmental issues, while taking into account valuable meanings for public space symbolic appropriation, sense of identification and ownership, recuperating and reinterpreting the heritage of twentieth–Century experiences such as Oscar Präger’s (naturalistic), Carlos Martner’s (cultural), Amereida’s (phenomenological) and Ritoque’s Open City
Keywords: Urban parks; chilean landscaping